Aplikasi Pupuk KNO3 dan NPK Pada Pertumbuhan Bibit Kelapa Sawit (Elaeis Guineensis Jacq.) Double Tone Di Main-Nursery. - Bambang Utoyo; Kresna Shifa Usodri; Yan Sukmawan; Ridho Esa Putra Arahman; Hamdani Hamdani; Albertus Sudirman (Politeknik Negeri Lampung., 2022)
One of the efforts that can be made to optimize the growth of double tone oil palm seedlings is to apply an appropriate combination of fertilization. The purpose of this study was to obtain the best KNO3 concentration and dose of NPK fertilizer in optimizing the growth of double tone oil palm seedlings in the main nursery. The research was carried out from December to July 2021. The research location was in the Oil Palm Seedling Business Unit of the Lampung State Polytechnic, Rajabasa, Bandar Lampung. This research was conducted using a factorial randomized block design (RAK) which was repeated 5 times. The first factor is the concentration of KNO3 fertilizer which consists of 3 levels, namely 0%, 2%, and 4%. The second factor is the dose of Compound NPK fertilizer which consists of 2 levels, namely 2.5 g and 5 g. Observations were made on the variables of seedling height, seedling diameter, leaf greenness, number of midribs and leaf area. Observational data were analyzed by F test at level =5%. If the results of the analysis of variance are significant, then it is continued with the smallest significant difference test (BNT) at the level of =5%. The results showed that the application of 4% KNO3 with a dose of 5 g compound NPK fertilizer showed the best results in optimizing the growth of double tone oil palm seedlings in the main nursery on all observation variables.